PENERAPAN MODEL (TSTS) DALAM MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS 9A DALAM MATERI RANGKAIAN LISTRIK DI SMP NEGERI PAKUSARI JEMBER TAHUN PELAJARAN 2019/2020 - Endah Noer Aini; Sri Marhaening Utami (Jurusan Pendidikan MIPA FKIP Universitas Jember, 2020)
Abstract: This research is motivated by the low participation of students or students' learning activities in the process of learning science class 9A in SMP Pakusari. Proses learning usually undertaken using direct instructional model that is delivering the materials to students as a whole and interspersed with exercises, learning like this causing students to tend to only acquire cognitive knowledge, not yet meaningful learning. This study is a Classroom Action Research (PTK) that uses the model and design of the Kemiss and Mc Taggart spirals. This study was conducted in 2 cycles implemented in the period from September to October 2019. Each cycle consisted of 4 stages, from the planning phase (planning), implementation, observation (observing) and reflection (reflecting). The data collection instruments in this study are student learning activity sheets, field notes and documentation in the form of photographs during the learning process. The results show an increase in student learning activities by using the two stay two stray model, namely speaking activities, writing activities and motor activities increased from cycle I with an average of 81.67 and cycle II with 85.00 final conclusion of this study that the application of learning model cooperative type two stay two stray can increase student learning activities. Keywords: Cooperative Learning Type Two Stay Two Stray, Student Learning Outcomes